PENGARUH MODEL PENJADWALAN PEMBELAJARAN DAN MOTIVASI BERPRESTASI TERHADAP HASIL BELAJAR PERAWATAN SEPEDA MOTOR SISWA SMK - Dedi Arsil Majid; Amat Mukhadis; Eko Edi Poerwanto (Teknologi dan Kejuruan, 2012)
The impact of learning schedulling model and achievement motivation to the learning result of motorcycle maintenance student of vocational high school. The purpose of this study to determine differences in learning outcomes among students who are taught using a block release and release hours, the students' motivation level high and low achievers, and their interactions. The research used true-experimental method. The research use ANOVA method for data analyzing. Results show that:      (1) there are significant differences in learning outcomes between the use of block release and hour release; (2) there are significant differences in learning outcomes between students with low achievement motivation and high achievement motivation; (3) no interaction between the scheduling model with achievement motivation; (4) the results of learning with block scheduling is superior release; (5) learning outcomes of students with high achievement motivation is superior.